Hungarian coins – Hebrew letters - Tóth, Csaba; Géza Kiss, József (KOINON: The International Journal of Classical Numismatic Studies, 2020)
Hungarian coins bore Latin inscriptions from the earliest times. Only in the nineteenth century did German-language, and during the 1848–1849 War of Independence, Hungarian-language legends appear. It is thus curious to find a group of thirteenth-century Hungarian coins bearing Hebrew letters (but not text!). Hebrew letters on Hungarian coins were first noted in the nineteenth century by Sámuel Kohn in his studies of the Hungarian Jewish history, and in some type-descriptions by László Réthy. Nonetheless, they only arose as a subject of research in the 1970s following the publication of a paper by Gyula Rádóczy drawing attention to them. Rádóczy systematically went through their various types, identified each Hebrew character, and attempted to link them with the initials of chamber counts known from written sources. He reached the conclusion that the ‘alef/aleph’ (א) was linked with Altman, the ‘chet’(ח) with Henoch, the ‘teth’ (ט) with Theka and the six-pointed star with Samuel. Soon, the investigation was joined by Sándor Scheibert and Lóránt Nagy, the latter attempting to date late Árpád-era coins relying on Rádóczy’s findings. Later, several papers tried to clarify the issue and determinate the persons of Jewish birth who could be linked with the coins.